Food and Drink at the Restoration, as seen through the diary, 1660-1669, of Samuel Pepys - Lehmann, Gilly (Petits Propos Culinaires, 1998)
The author employed computational analysis techniques in a study of what Samuel Pepys says in his diaries that he consumed between 1660-1669.